2022
DOI: 10.1002/advs.202201678
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Durable Sodium, Chloride‐doped Iron Oxide‐Hydroxide Nanohybrid‐Promoted Capacitive Deionization of Saline Water via Synergetic Pseudocapacitive Process

Abstract: Recently, the rational design and development of efficient faradaic deionization electrodes with high theoretical capacitance, natural abundance, and attractive conductivity have shown great promise for outstanding capacitive deionization (CDI)‐based desalination applications. Herein, the construction of novel FeOOH hybrid heterostructures with Na and Cl dopants (e.g., Na‐FeOOH and Cl‐FeOOH) via a robust hydrothermal strategy is reported, and an asymmetric CDI cell (Na‐FeOOH//Cl‐FeOOH) comprising Na‐FeOOH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 60 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…Especially, such a high MSAR value for N, P-GC/ MXene indicated that the desalination of NaCl could be rapidly accomplished in a short time, which was very essential for the desalination process of actual water. 8,9 Furthermore, we also studied the areal SAC of N, P-GC/MXene under different mass loadings. The results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, such a high MSAR value for N, P-GC/ MXene indicated that the desalination of NaCl could be rapidly accomplished in a short time, which was very essential for the desalination process of actual water. 8,9 Furthermore, we also studied the areal SAC of N, P-GC/MXene under different mass loadings. The results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Capacitive deionization (CDI) with merits such as low energy consumption, ease of operation, and environmental friendliness, has attracted considerable attention for saline water desalination, especially for low-salinity solutions. [5][6][7][8] Electrode materials are known to play a signicant role in achieving high efficiency, rapid desalination rate, and excellent cycling stability for CDI, and thereby the design and innovation of advanced electrode materials have always been a research hotspot. 9,10 Generally, CDI electrode materials can be divided into two categories: (I) electrochemical double-layer (EDL) capacitive materials, e.g., carbon materials like activated carbon (AC), 11 porous carbon, 12 graphene, 13 and carbon nanotubes (CNTs); 14 (II) pseudocapacitive materials such as metal oxides, 15 suldes, 16 and hydroxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshwater scarcity heavily harms the sustainable development of society, and energy-efficient technology is therefore critically in demand to tackle this challenge . Capacitive deionization (CDI) is a robust process for producing clean water from brackish water with low energy input and high efficiency. The most important part of CDI is the electrode, which determines the desalination performance. In recent years, CDI faradic electrodes emerged as a hot topic due to their strong deionization ability. While several materials have been explored for the selective removal of sodium (Na + ) ions, faradic materials for the removal of chloride (Cl – ) ions are limited . Materials like Ag and Bi, which are often used for Cl – capture, face challenges like high costs and poor cycle performance. , …”
Section: Introductionmentioning
confidence: 99%
“…In pursuit of efficient and stable CDI performance, many efforts have been focused on the optimization and innovation of devices and electrode materials, suggesting that CDI performance is closely related to electrode materials. , The traditional Cl-storage electrodes are carbon materials based on the electric double-layer mechanism, such as porous carbon, carbon nanotubes, graphene, and so forth. However, the lower adsorption capacity (3–20 mg g –1 ) and co-ion repulsion effect of carbon materials seriously hinder their further CDI applications. Recently, several explorations have been made in redox pseudocapacitance-based Cl-storage electrodes, which exhibit stronger electro-absorption capacity, a faster adsorption rate, and better stability. Particularly, iron-/nitrogen-doped carbon (Fe/NC) hybrid composites with abundant sources, environmental friendliness, high conductivity, and rich valence states have shown great potential as an efficient electrode for batteries, supercapacitors, and CDI applications. For instance, Wang et al have prepared a Fe–N–C composite that exhibits a desalination capacity of 36.25 mg g –1 and good regeneration ability in 30 cycles . A three-dimensional (3D)-FeNC tube has been constructed for CDI electrodes, which demonstrates a high capacity of 40.70 mg g –1 and stable cycling over 200 cycles .…”
Section: Introductionmentioning
confidence: 99%